The Mispricing of U.S. Treasury Bonds: A Case Study - Cornell, Bradford; Shapiro, Alan C. (Review of Financial Studies, 1989)
This article documents an apparent pricing anomaly involving 94 percent, 30-year Treasury bonds during the months of May and June 1986. During this period, the price of the 94s rose sharply relative to the prices of other long-term Treasury bonds and created a potential arbitrage opportunity. In addition, owners of the 94 bonds were able to borrow at a zero interest rate bypledging their bonds. Detailed examination reveals that this relative pricing anomaly cannot be attributed to changes in the level or term structure of interest rates or to differences between the bonds with respect to liquidity, taxation, or duration.